2006
DOI: 10.1111/j.1467-9922.2006.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Learning and Cultural Representations: Beyond Competence and Identity

Abstract: The socio-contextual model of second language (L2) learning proposes that L2 learning is influenced by aspects of contact with the L2 community, L2 confidence, and identification to both the first language and L2 community (Clément, 1980;. The present study examines how these aspects are linked to individuals' cultural representations, corresponding to attitudes toward the L2 community (Sperber, 1996). Respondents included Francophone (n = 50) and Anglophone (n = 50) university students with low and high ethno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 19 publications
5
25
2
4
Order By: Relevance
“…Se constituyen, a su vez, como sistemas de códigos, valores, lógicas clasificatorias, principios interpretativos y orientadores de las prácticas, que definen la llamada conciencia colectiva, la cual se rige con fuerza normativa en tanto instituye los límites y las posibilidades de la forma en que las mujeres y los hombres actúan en el mundo. (p. 11) Por su parte, Rubenfeld, Clément, Lussier, Lebrun, & Auger (2006) sugieren que las representaciones sociales se forman a través del discurso y la interacción. Asimismo, Araya (2002, p. 9) afirma que se trata de una noción que unifica e integra lo individual y lo colectivo, lo simbólico y lo social; el pensamiento y la acción", lo cual complejiza la noción de representación.…”
Section: Representaciones Socialesunclassified
See 1 more Smart Citation
“…Se constituyen, a su vez, como sistemas de códigos, valores, lógicas clasificatorias, principios interpretativos y orientadores de las prácticas, que definen la llamada conciencia colectiva, la cual se rige con fuerza normativa en tanto instituye los límites y las posibilidades de la forma en que las mujeres y los hombres actúan en el mundo. (p. 11) Por su parte, Rubenfeld, Clément, Lussier, Lebrun, & Auger (2006) sugieren que las representaciones sociales se forman a través del discurso y la interacción. Asimismo, Araya (2002, p. 9) afirma que se trata de una noción que unifica e integra lo individual y lo colectivo, lo simbólico y lo social; el pensamiento y la acción", lo cual complejiza la noción de representación.…”
Section: Representaciones Socialesunclassified
“…Las representaciones tienen la capacidad de dirigir nuestros comportamientos, así como la forma en la que establecemos relaciones con otros (Rubenfeld, Clément, Lussier, Lebrun, & Auger, 2006). Sin embargo, a pesar de la relación que se ha establecido entre representaciones y prácticas, Billiez y Millet (2001) afirman que la influencia de las primeras en el actuar y en las prácticas lingüísticas es compleja y a veces contradictoria.…”
Section: Representaciones Socialesunclassified
“…Les liens sociopsychologiques ainsi que les questions identitaires, de motivation et attitudes sont largement documentées dans nombre de publications (Clément, 1984;Dörnyei, 1994;MacFarlane, 1997;Noel, 2005;Rubenfeld et al, 2006), alors que les défis touchant l'apprentissage des langues et l'impact dans les milieux multilingues sont traités par d'autres auteurs (Valdes, 2005(Valdes, , 1995Kramsch et Whiteside, 2007). Pour ce qui est des méthodologies d'enseignement des langues internationales dans des contextes postsecondaires, dans différents pays, il est intéressant de consulter certains auteurs (Schwartzer, 2001;Schwarzer et Petrón, 2005;Husseinali, 2006;Byrnes, 2007Byrnes, , 2008Pratt et al, 2008).…”
Section: Le Cadre De L'acquisition Des Langues éTrangères En Généralunclassified
“…How the process of L2-learning relates to the ways in which L2 learners view the L2 community is the object of the study by Rubenfeld et al (2006).They claim it is already known that contact with an L2 group can help build up confidence in the individual's L2 and feelings of identification with the L2 community, but that thus far research had not shown how cultural representations in the form of attitudes and beliefs about the L2 community are formed. Their subjects were 50 anglophone and 50 francophone university students in Canada.…”
Section: Cultural Representationmentioning
confidence: 99%